Influence of budgetary slack and elements of the budgetary process on perceptions of justice, - Vanderlei dos Santos (Revista Contabilidade & Finanças, 2022)
ABSTRACT This study examined the relationships between elements of the budgetary process (budgetary participation, the use of budgetary goals for performance assessments, and the use of budgetary goals for variable remuneration purposes), budgetary slack, and perceptions of justice, on the assumption that budgetary slack is an antecedent of perceptions of justice and acts as an intervening variable between elements of the budgetary process and perceptions of justice. Studies addressing the relationship between justice and slack have not considered the positive aspects derived from budgetary slack such as necessary and emergency resources. Moreover, most of these studies have focused on procedural justice and on an element of the budgetary process (budgetary participation), to predict feelings of justice and the creation of slack. The results of the study suggest alternative conceptions for analyzing the relationship between perceptions of justice and budgetary slack, going beyond the economic lens for the latter. By resorting to social exchange theory (SET), a perspective is provided on how elements of the budgetary process affect managers’ perceptions of justice and how budgetary slack, as an economic and social exchange resource, shapes those effects. Although researchers have already pointed to budgetary slack as being beneficial for the organization, no studies were found that have analyzed it as a predictor of perceptions of justice. A survey was conducted with a sample of 114 company managers and the hypotheses were tested with the application of structural equation modeling. The results reveal that budgetary slack is an inherent element of the budgetary process, conceived as an economic and socioemotional resource, according to the principles of SET, and used by organizations with a view to greater perceptions of justice. Budgetary slack is essential for predicting managers’ feelings of distributive and procedural justice regarding the budgetary process.